Enhancing the conversion efficiency of extreme ultraviolet light sources using a 2 µm wavelength laser. (16th December 2021) - Yuan, Y; Ma, Y Y; Wang, W P; Chen, S J; Cui, Y; Zi, M; Yang, X H; Zhang, G B; Leng, Y X
Abstract: In this study, we use the FLASH radiation hydrodynamic code and the FLYCHK atomic code to investigate the energy conversion and spectra associated with laser–Sn target interactions with 1 and 2 µ m wavelength lasers. We found that the conversion efficiency (CE) reached as much as 3.38% with the 2 µ m laser, which is 1.48 percentage points higher than the 1 µ m laser (CE = 1.9%). In addition, we analyzed the contribution of dominant ionization states to the emission spectrum for both lasers. We observed that the growths of the out-of-band emission eventually led to a broadening of the spectrum, resulting in a reduction of spectral purity for the 1 µ m laser. By contrast, the emission main peaks were all centered near 13.5 nm for the 2 µ m laser, which is beneficial for efficient emission of light with a 13.5 nm wavelength (relevant for nanolithographic applications).